Effect of contrasting crop rotation systems on soil chemical and biochemical properties and plant root growth in organic farming: First results - Monaci, Elga; Polverigiani, Serena; Neri, Davide; Bianchelli, Michele; Santilocchi, Rodolfo; Toderi, Marco; D'Ottavio, Paride; Vischetti, Costantino (Italian Journal of Agronomy, 2017)
Organic farming is claimed to improve soil fertility. Nonetheless, among organic practices, net C-inputs may largely vary in amount and composition and produce different soil conditions for microbial activity and plant-root system adaptation and development. In this study, we hypothesised that, in the regime of organic agriculture, soil chemical and biochemical properties can substantially differ under contrasting crop rotation systems and produce conditions of soil fertility to which the plant responds through diverse growth and production. The impact of 13 years of alfalfa-crop rotation (P-C) and annual crop rotation (A-C) was evaluated on the build up of soil organic carbon (SOC), active (light fraction organic matter, LFOM; water soluble organic carbon, WSOC) and humic fraction [fulvic acids carbon (FAC), humic acids carbon (HAC)], soil biochemical properties [microbial biomass carbon (MBC), basal respiration (dBR), alkaline phosphatase (AmP), arylsulfatase (ArS), orto-diphenoloxidase (o- DPO)] and the amount of available macro-nutrients (N, P, and S) at two different soil depths (0-10 cm and 10-30 cm) before and after cultivation of wheat. We also studied the response of root morphology, physiology and yield of the plant-root system of wheat. Results showed that the level of soil fertility and plant-root system behaviour substantially differed under the two crop rotation systems investigated here. We observed high efficiency of the P-C soil in the build up of soil organic carbon, as it was 2.9 times higher than that measured in the A-C soil. With the exception of o-DPO, P-C soil always showed a higher level of AmP and ArS activity and an initial lower amount of available P and S. The P-C soil showed higher rootability and promoted thinner roots and higher root density. In the P-C soil conditions, the photosynthesis and yield of durum wheat were also favoured. Finally, cultivation of wheat caused an overall depletion of the accrued fertility of soil, mainly evident in the P-C soil, which maintained a residual higher level of all the chemical and biochemical properties tested.